1991
DOI: 10.3109/17453679108993085
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the knee: Diagnosis and outcome in 40 patients

Abstract: Clinically suspected primary osteonecrosis of the knee was studied in 40 patients with repeated plain radiography and scintimetry, and the patients were followed for 1-7 years. Thirty-three patients had typical scintimetric and radiographic signs of osteonecrosis of either one of the femoral condyles, whereas 7 patients had only typical scintimetric findings, but never developed an osteonecrosis based on plain radiography. Because the scintimetric findings were identical to the other 33 knees and because there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
0
26
2
3
Order By: Relevance
“…The size can be measured by either the ratio [16] or the area [17] technique. Studies have shown that there is no difference between the two methods in predicting prognosis [18,19]. We used the ratio method and classified a lesion as being large if it involved more than 0.32 of the involved condyle width.…”
Section: Radiographic Resultsmentioning
confidence: 99%
“…The size can be measured by either the ratio [16] or the area [17] technique. Studies have shown that there is no difference between the two methods in predicting prognosis [18,19]. We used the ratio method and classified a lesion as being large if it involved more than 0.32 of the involved condyle width.…”
Section: Radiographic Resultsmentioning
confidence: 99%
“…Jureus et al 60 reported 40 patients with mean follow-up of 9 yr and showed a 75% incidence of radiographic osteoarthritis and that 42.5% required either arthroplasty or osteotomy. Al-Rowaih et al 18 similarly followed 40 patients from 1-7 yr and reported that 72.5% developed osteoarthritis and 30% required either an arthroplasty or osteotomy. Only one of the case series 52 reported the incidence of osteoarthritis on radiographic follow-up and reported that at between 1-4 yr 59% had evidence of osteoarthritis radiographically, which is comparable to the previous reports referenced given the differing lengths of follow-up.…”
Section: Postarthroscopic Osteonecrosismentioning
confidence: 87%
“…Only one of the case series 52 reported the incidence of osteoarthritis on radiographic follow-up and reported that at between 1-4 yr 59% had evidence of osteoarthritis radiographically, which is comparable to the previous reports referenced given the differing lengths of follow-up. 18,60 Two studies commented on the requirement for surgery after bisphosphonate treatment, and this ranged from 7-12%, although the follow-up in these studies ranged from 6 mo to 4 yr, limiting comparison to the referenced papers. 50,52 The type of outcomes recorded varied in type and quality, the use of a validated knee PROM would have been optimal and was only recorded in the randomized controlled trials 51 where it was a secondary outcome measure.…”
Section: Postarthroscopic Osteonecrosismentioning
confidence: 97%
See 1 more Smart Citation
“…But even in such cases, progression can not always be successfully hindered, and patients with severe necrotic changes may require surgical intervention (e.g., high tibial osteotomy or total knee replacement). 2,[8][9][10] In this context and in consideration of the basic research on the biostimulatory effects of low-level laser therapy (LLLT) on microcirculation and vascularization as well as on osteogenesis, and its clinical effectiveness in bone and joint diseases such as osteoarthritis and rheumatoid arthritis, we propose LLLT as a promising therapeutic option for patients with SONK. [11][12][13][14][15][16] However, clinical data on its effectiveness are currently lacking.…”
Section: Introductionmentioning
confidence: 99%